Uma análise dos impactos de despesas públicas sobre a pobreza e a desigualdade nos estados brasileiros - Silva, Ivanildo Lopes da (2012)
The state aims to meet social needs, promote an efficient use of resources and improve income distribution. However, the degree of income inequality in Brazil is still very high and is one of the main indicators of social inequality, thus requiring reexamining the mechanisms to protect people and promote socio-economic development. From this premise, this study analyzed the effects of public expenditure in relation to indicators of poverty and income inequality in the Brazilian states in the period 2005 to 2009, identifying which variables were most influential to the improvement of these indicators in the period. The theoretical reference includes chapters on Economic Growth and Income Inequality, Public Expenditure and Social and Public Policy in Brazil. The study was made using data and information from the Institute of Applied Economic Research – IPEA and the Brazilian Institute of Geography and Statistics – IBGE, and the relationship of selected variables with indicators of poverty and inequality is demonstrated empirically by estimating the elasticities using regressive cross-section models. This model was chosen because of its clear interpretation, allowing support the development of policies aimed at reducing inequality in the states. The results show that the advances were discrete in time for some of the indicators selected, being more significant for those with policies relating to proposals to transfer income and poverty reduction, which contributed to the fall of the poor and indigent and increased income, indicating that well-focused programs are better inducers of social progress.